2023
DOI: 10.1021/acs.jmedchem.3c00460
|View full text |Cite
|
Sign up to set email alerts
|

To Fold or Not to Fold: Diastereomeric Optimization of an α-Helical Antimicrobial Peptide

Hippolyte Personne,
Thierry Paschoud,
Sofia Fulgencio
et al.

Abstract: Membrane disruptive α-helical antimicrobial peptides (AMPs) offer an opportunity to address multidrug resistance; however, most AMPs are toxic and unstable in serum. These limitations can be partly overcome by introducing D-residues, which often confers protease resistance and reduces toxicity without affecting antibacterial activity, presumably due to lowered α-helicity. Here, we investigated 31 diastereomers of the α-helical AMP KKLLKLLKLLL. Three diastereomers containing two, three, and four D-residues show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Peptoid units can be introduced during standard Fmoc solid-phase peptide synthesis (Fmoc-SPPS) using the so-called submonomer strategy, which consists in bromoacetylation of the N -terminus of the growing chain followed by substitution of the bromide using an excess of a primary amine, here isobutylamine for a leucine peptoid unit ( N Leu) or tert -butyl (4-aminobutyl)­carbamate for a lysine peptoid unit ( N Lys). We prepared the eleven selected peptide–peptoid hybrids together with undecapeptides ln65 and ln69 , as well as the PrAMP oncocin, to be used as positive controls, using high-temperature (60 °C) semiautomated Fmoc-SPPS on Rink amide resin in DMF with di-isopropyl carbodiimide (DIC) and OxymaPure as coupling reagents as described previously. , Addition of amino acids was repeated twice, while acylation with bromoacetic acid and displacement with the primary amine were performed only once. All products were obtained in pure form by acidic cleavage and deprotection followed by preparative reversed-phase HPLC (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Peptoid units can be introduced during standard Fmoc solid-phase peptide synthesis (Fmoc-SPPS) using the so-called submonomer strategy, which consists in bromoacetylation of the N -terminus of the growing chain followed by substitution of the bromide using an excess of a primary amine, here isobutylamine for a leucine peptoid unit ( N Leu) or tert -butyl (4-aminobutyl)­carbamate for a lysine peptoid unit ( N Lys). We prepared the eleven selected peptide–peptoid hybrids together with undecapeptides ln65 and ln69 , as well as the PrAMP oncocin, to be used as positive controls, using high-temperature (60 °C) semiautomated Fmoc-SPPS on Rink amide resin in DMF with di-isopropyl carbodiimide (DIC) and OxymaPure as coupling reagents as described previously. , Addition of amino acids was repeated twice, while acylation with bromoacetic acid and displacement with the primary amine were performed only once. All products were obtained in pure form by acidic cleavage and deprotection followed by preparative reversed-phase HPLC (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, for those AMPs in both models 1 and 2, the impact of “helix breakers” on the structural and biological properties varies depending on each case. For example, stereorandomized derivative 23 of peptide 21 and its all‐D‐enantiomeric 22 ( both in model 1A and 2B) , the antibacterial activity was only slightly decreased whereas the minimum hemolysis concentration (MHC) was notably increased, thus indicating a significant improvement in selectivity [4a] . This interesting data suggested that many mutants among all the 1024 possible diastereometers that have better activity than both peptides 21 and 22 .…”
Section: The Influence Of Amphipathic Design To the Structure And Act...mentioning
confidence: 90%
“…This interesting data suggested that many mutants among all the 1024 possible diastereometers that have better activity than both peptides 21 and 22 . Then, a diastereomeric series of 21 was prepared to further examine the structure‐activity relationships [4a] . In terms of secondary structure, there are two directions observed.…”
Section: The Influence Of Amphipathic Design To the Structure And Act...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of developing computational tools for new modalities including beyond-Ro5 molecules [ 24 , 25 ], in our case for peptides with variable chain topology and stereochemistry [ 26 28 ], we have adapted molecular fingerprints based on atom-pairs [ 29 32 ] for large molecules such as peptides and proteins [ 33 35 ]. In particular, we combined atom-pair analysis and circular substructures as encoded by the Morgan fingerprint ECFP4 [ 36 , 37 ], with the principle of data compression using MinHashing [ 38 41 ], to design MAP4, a MinHashed Atom-Pair fingerprint.…”
Section: Introductionmentioning
confidence: 99%